ANALISIS PRESUPOSISI DAN IMPLIKATUR PADA DISKUSI WHATSAPP GRUP MATA KULIAH TEORI DAN APRESIASI SASTRA PASCASARJANA UNIVERSITAS INDRAPRASTA PGRI - Maguna Eliastuti; Alfi Nurhasanah; Damaji Ratmono; Ira Riza Sadeva Chan; Sarnita; Siti Jubaedah (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
Introduction. Theory and Appreciation of Literature course at Indraprasta University PGRI is a course for postgraduate students majoring in Indonesian. This course is conducted online (in the network), namely by utilizing the Whatsapps (WA) application by forming a WhatsApp group for the course. During the course of the course there is interaction between lecturers and students, namely in the form of discussions about the themes raised every week. Research purposes. The purpose of this research is to find out how presuppositions and speech implicatures are in whatsapp group discussions for Literary Theory and Appreciation courses. The research approach is with a qualitative approach and descriptive method. The object in this research is the form of presuppositions and speech implicatures resulting from group discussion utterances, while the subject in the research is lecturer and student discussions in WhatsApp groups. Data collection techniques were observation, interviews, recording techniques, and free-involved listening techniques and note-taking techniques. Data analysis using the Miles and Huberman method. The results of this study are (1) Speech presuppositions found in lecturer and student WA group discussions, namely potential presuppositions, namely containing noun phrases where the lecturer conveys the learning situation that will begin, factive presuppositions, structural presuppositions, lexical presuppositions, all of which are indicated by several conversations between lecturers and students, (2) Speech implicatures found in WA group discussions are conventional implicatures and conversational implicatures.